Relationship between Glycemic Load and Blood Lipid Level in Hospitalized Adult Chinese - Hui Li; Haifeng Liu; Jinhong Chen; Li Li; Huanyu Wang; Jing Li; Lei Wang (Tehran University of Medical Sciences, 2015)
Background: Metabolic diseases in China have been on the rise in recent decades, partially due to reduced cereal consumption and excessive intake of low glycemic index (GI) foods such as meat and oil. Although the relationship between dietary glycemic load (GL) and various metabolic diseases has been extensively studied worldwide, it is unclear whether dietary GL is related to blood lipid levels and dyslipidemia risk in Chinese. The aim of the present study was to investigate the relationship between dietary GL and blood lipid levels and dyslipidemia risk in hospitalized Chinese adults. Methods: Dietary GL in 2258 hospitalized Chinese adults was calculated based upon GI, carbohydrate content and daily intake of individual foods. In addition, fasting total cholesterol (TC), triglycerides (TG), HDL cholesterol (HDLC) and LDL cholesterol (LDL-C) data were collected. Multiple regression and logistic regression analysis were used to determine the relationship between dietary GL and plasma lipid levels or dyslipidemia risk. Results: Dietary GL remained inversely associated with blood total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) (P0.01). With increasing dietary GL, risks of hypercholesterolemia and high blood LDL-C were significantly reduced (P0.01). In the meantime dietary GL remained negatively associated with blood triglyceride (TG) and high-density lipoprotein cholesterol (HDL-C) (P0.01), but showed no significant influence on risk of hypertriglyceridemia and low blood HDL-C (P0.05). Conclusion: High GL diet, as represented by traditional Chinese dietary pattern, may contribute to reduced risk of dyslipidemia in Chinese adults.